2015
DOI: 10.11604/pamj.2015.21.301.4636
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Kell phenotype among pregnant women in Sokoto, North Western Nigeria

Abstract: IntroductionKell antigen is highly immunogenic and is the common cause of antibody production in mismatched blood transfusions, haemolytic transfusion reaction (HTR) and maternal alloimmunization, which causes severe anaemia in neonates. The aim of this study is to determine the prevalence and ethnic variation of the Kell phenotype among pregnant women in Sokoto, Nigeria.MethodsKell antigen status of 150 pregnant women aged 18-45 years and mean age 27.19 ±4.69 years attending antenatal clinic in UDUTH Sokoto N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
(36 reference statements)
2
7
0
Order By: Relevance
“…Unlike the Rh antigens, there are minimal reports on the distribution of K in Nigeria and no reports on the prevalence of other clinically significant Kell antigens. In our study cohort, no participants were positive for K. This finding is in agreement with the two existing studies of K in Nigeria (reported prevalence of 1% 15 to 2% 12,13 ) and what is reported for black populations in the United States. Notably, in our study cohort, the prevalence of all RBC antigens was not statistically correlated with ethnicity.…”
Section: Rh and Kell Blood Group Antigens In Nigeriasupporting
confidence: 93%
“…Unlike the Rh antigens, there are minimal reports on the distribution of K in Nigeria and no reports on the prevalence of other clinically significant Kell antigens. In our study cohort, no participants were positive for K. This finding is in agreement with the two existing studies of K in Nigeria (reported prevalence of 1% 15 to 2% 12,13 ) and what is reported for black populations in the United States. Notably, in our study cohort, the prevalence of all RBC antigens was not statistically correlated with ethnicity.…”
Section: Rh and Kell Blood Group Antigens In Nigeriasupporting
confidence: 93%
“…The Kell antigen is a very immunogenic antigen, and anti‐K often appears after transfusion with Kell‐positive RBCs . Of 98 pregnancies in which anti‐K was detected in our study, 65 (66%) involved women who had previously received transfusions.…”
Section: Discussionmentioning
confidence: 68%
“…For this reason Osaro et al (2015) conducted a research to know the KELL distribution in pregnant women in Sokoto, point out that there is a need for routine screening for clinical significance antibodies in pregnant women, as well as recommend that in the first prenatal visit must be held research to the most immunogenic antigens (24). The study also suggested to stock up negative K1 erythrocytes units for use in all pregnant women and women of childbearing age who require transfusion.…”
Section: Resultsmentioning
confidence: 99%